Management of common bile duct stones: a comprehensive review - Wang, Xiaojun; Li, Zhifeng (Frontiers in Surgery, 2025)
CBD stones impose significant morbidity and cost. This review compares the efficacy and safety of endoscopic sphincterotomy (EST) and laparoscopic common bile duct exploration (LCBDE) and summarizes emerging techniques and remaining controversies. While EST remains a cornerstone for rapid stone extraction, particularly in high-risk surgical candidates, its association with post-procedural pancreatitis and long-term sphincter dysfunction underscores the need for judicious patient selection. Conversely, LCBDE emerges as a compelling alternative, offering superior complete stone clearance rates for larger or complex stones, reduced post-procedural pancreatitis, and the unique advantage of direct biliary tree visualization. However, its technical demands and bile leak risk necessitate standardized training protocols and institutional expertise. The review further explores cutting-edge adjunctive therapies, including SpyGlass cholangioscopy for impacted stones, extracorporeal shock wave lithotripsy (ESWL) for large calculi, and artificial intelligence-driven procedural planning, which collectively herald a new era of precision medicine in biliary surgery. Notably, hybrid approaches such as intraoperative endoscopic retrograde cholangiopancreatography (ERCP) demonstrate promising outcomes in reducing hospitalization and postoperative complications, albeit requiring multidisciplinary team coordination. Despite these advances, critical knowledge gaps persist regarding long-term functional outcomes of EST, cost-effectiveness of emerging technologies, and optimal management of anatomically complex cases. The lack of robust randomized trials comparing EST and LCBDE in diverse patient cohorts limits contemporary guideline development, underscoring the urgent need for high-quality comparative effectiveness research. This review synthesizes current evidence to advocate for a personalized, algorithmic approach to CBD stones management, balancing procedural risks, stone characteristics, and institutional capabilities. By highlighting translational research opportunities and unmet clinical needs, it provides a roadmap for advancing minimally invasive biliary surgery while challenging the global hepatobiliary community to prioritize patient-centered innovation and rigorous outcomes research.